The Aqueous Chemistry of the Copper-Ammonia System and Its Implications for the Sustainable Recovery of Copper - Velasquez-Yevenes, L (Elsevier Ltd, 2022)
The dissolution of copper during the leaching of chalcopyrite in ammonia solutions is an attractive alternative to acid sulfate leaching in the treatment of ores with high consumption of acid. Despite considerable research into this complex leaching system, a lack of understanding of the fundamental chemical drivers has delayed the implementation of the ammonia process. In the present study, various ammonium salts solutions (chloride, sulfate, carbonate) have been used to study the effect of ion association on the dissociation constant of the ammonium ion at temperatures of 25 and 35 °C. Experimental and calculated solubilities of Cu2+ have been obtained under different conditions and plotted in speciation distribution diagrams, in other to assess the accuracy of predictions using available thermodynamic properties. Ion association was found to significantly affect the dissociation constant of the ammonium ion in solutions containing sulfate, chloride and carbonate anions; thus, influencing the free ammonia concentration in solution. Increasing temperature from 25 to 35 °C was found to decrease the dissociation constant of the ammonium ion. These findings highlight the importance of using the correct anionic ligands for the ammonium ions and temperature in order to obtain high dissolution of copper. It has been established that solubility of copper in ammonia solution is affected by the anionic ligands, temperature and addition of chloride ions. The NH3 ligand forms strong coordination compounds with cupric or cuprous ions depending on the anionic ligand, generating an increase in solubility between pH 8.5 and 10.0. The present study, therefore, identifies important constraints on the role of varying anion associated with ammonia, temperature, pH, and addition of chloride ions and the inter-dependence of these factors in controlling Cu2+ solubility in ammoniacal systems. The results from the present study provides experimental pKa values and solubility constants of the various ammoniacal systems to provide commercial processing via ammoniacal routes the optimal conditions in which to maximise Cu recovery and maintain free ammonia at levels to minimise volatility and loss. The findings are directly beneficial to future commercial application employing effective ammonium-anion lixiviant strategies in the sustainable recovery of Cu. © 2022 The Authors